Implicit Statistical Learning in Naturalistic and Instructed Morphosyntactic Attainment: An Aptitude‐Treatment Interaction Design. Issue 4 (10th July 2021) - Bolibaugh, Cylcia; Foster, Pauline
Abstract: We investigated the potential influence of implicit learning mechanisms on L2 morphosyntactic attainment by examining the relationship between age of onset (AoO), two cognitive abilities hypothesized to underlie implicit learning (phonological short‐term memory and implicit statistical learning), and performance on an auditory grammaticality judgment test (GJT). Participants were 71 Polish‐English long‐term bilinguals with a wide range of AoOs (1–35 years) who differed in their context of learning and use (immersed vs. instructed). In immersed learners, we observed a growing dissociation between performance on grammatical and ungrammatical sentences as AoO was delayed. This effect was attenuated in those with better phonological short‐term memory and statistical learning abilities and is consistent with a decline in the ability to learn from implicit negative evidence. In instructed learners, GJT performance was subject to additive effects of AoO and grammaticality and was not associated with either cognitive predictor, suggesting that implicit learning mechanisms were not involved. Abstract :